Psychometric properties of 2-minute walk test: a systematic review - Pin, Tamis W (Archives of physical medicine and rehabilitation, 2014)
To systematically review the psychometric evidence on the 2-minute walk test (2MWT). Electronic searches of databases including MEDLINE, CINAHL, Academic Search Premier, SPORTDiscus, PsycINFO, EMBASE, the Cochrane Library, and DARE were done until February 2014 using a combination of subject headings and free texts. Studies were included if psychometric properties of the 2MWT were (1) evaluated; (2) written as full reports; and (3) published in English language peer-reviewed journals. A modified consensus-based standard for the selection of health measurement instruments checklist was used to rate the methodological quality of the included studies. A quality assessment for statistical outcomes was used to assess the measurement properties of the 2MWT. Best-evidence synthesis was collated from 25 studies of 14 patient groups. Only 1 study was found that examined the 2MWT in the pediatric population. The testing procedures of the 2MWT varied across the included studies. Reliability, validity (construct and criterion), and responsiveness of the 2MWT also varied across different patient groups. Moderate to strong evidence was found for reliability, convergent validity, discriminative validity, and responsiveness of the 2MWT in frail elderly patients. Moderate to strong evidence for reliability, convergent validity, and responsiveness was found in adults with lower limb amputations. Moderate to strong evidence for validity (convergent and discriminative) was found in adults who received rehabilitation after hip fractures or cardiac surgery. Limited evidence for the psychometric properties of the 2MWT was found in other population groups because of methodological flaws. There is inadequate breadth and depth of psychometric evidence of the 2MWT for clinical and research purposes-specifically, minimal clinically important changes and responsiveness. More good-quality studies are needed, especially in the pediatric population. Consensus on standardized testing procedures of the 2MWT is also required.